The Heritage of the Arabian Mission of the Reformed Church in America, the Omani Context, and the Work of Al Amana Centre - Meyers, Justin (Reconciliation, Heritage and Social Inclusion in the Middle East and North Africa, 2022)
The setting of the Sultanate of Oman combined with the heritage of the Arabian Mission of the Reformed Church in America has created a unique context for the work of the Al Amana Centre. This article will explore the history and modern-day experience of tolerance and pluralism in Oman, the historical, theological movements of the Reformed Church in America missionaries toward a more accepting view of Islam, and how these two combine to create opportunities for participants in Al Amana Centre’s programing to discover and experience reconciliation. This article will draw upon scholars who have a long history with Oman, the stories and history of the Arabian Mission, and accounts of the current work of Al Amana Centre.
Keywords: Missionnaires – Oman